Four haplotype blocks linked to Ascochyta blight disease resistance in chickpea under Mediterranean conditions - Carmona, Alejandro; Rubio, Josefa; Millan, Teresa; Gil, Juan; Die, Jose V.; Castro, Patricia (Frontiers in Plant Science, 2023)
Ascochyta blight, caused by the fungal pathogen Ascochyta rabiei, is a devastating biotic stress that poses a significant threat to chickpea cultivation worldwide. To combat this disease, breeding programs have focused on developing cultivars with resistance to Ascochyta blight. However, a comprehensive understanding of the underlying plant defense mechanism is still lacking. To identify genomic regions associated with resistance, a recombinant inbred line (RIL) population was created by crossing ILC3279 (kabuli, resistant) and WR315 (desi, susceptible), which was then phenotyped and sequenced using a tuneable genotyping-by-sequencing (tGBS) protocol to obtain single nucleotide polymorphisms (SNPs). Our analysis identified four genomic regions associated with Ascochyta blight resistance in chromosomes 2 and 4, among which a region spanning from 3.52 to 8.20 Mb in chromosome 4 was the most robust candidate for resistance, being associated with resistance in both years and populations. We further validated the association of genomic regions with Ascochyta blight resistance in a second recombinant inbred line population derived from the cross between JG62 (desi, susceptible) and ILC72 (kabuli, resistant). A total of 30 genes from the identified regions were selected as robust candidates, and LOC101507066, which encodes a leucine-rich repeat receptor-like protein kinase, was the most robust candidate gene, as it plays critical roles in plant stress responses and immunity. Our findings have potential to accelerate marker-assisted genetic improvement and facilitate the development of integrated strategies for crop protection.